COVID-19: Loss of bridging between innate and adaptive immunity? (2020)
COVID-19 has spread to most countries in the world. However, there are some striking differences in how COVID-19 is behaving in different age groups. While data on COVID-19 is limited, children appear to be less susceptible to severe disease. These unique characteristics may be considered as a potential link to understanding the immune system and response in COVID-19 and lead to an effective cure to the disease. We suggest a possible role of loss of bridging between innate and adaptive immunity in COVID-19 and a potential treatment modality also discussed.